The Effect of Gender Towards Self-Discipline Attitudes and Student Learning Outcomes in Physics - Melyana Dyah Anggraeni; Widha Sunarno; Suparmi Suparmi (Pascasarjana Universitas Negeri Malang (UM), 2020)
Abstract: This study aims to determine the effect of gender towards self-discipline attitudes and student learning outcomes in Physics, the effect of self-discipline attitudes towards student learning outcomes in Physics. This is comparative method. The population is 86 of XI grade students of Public Senior High School 2 and 7 of 2019/2020 school year. Data collection was done using questionnaires, tests, and documentation methods. The results conclude that there is an effect of gender towards students’ self-discipline attitudes; no effect of gender towards student learning outcomes in Physics; no effect of self-discipline attitudes towards student learning outcomes. Key Words: gender, self-discipline attitudes, physics learning outcomesAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh jenis kelamin terhadap sikap disiplin diri dan hasil belajar fisika siswa, pengaruh sikap disiplin diri terhadap hasil belajar fisika siswa. Penelitian ini menggunakan metode komparatif. Populasi dalam penelitian ini adalah siswa kelas XI SMA Negeri 2 dan 7 tahun pelajaran 2019/2020 yang berjumlah 86 siswa. Pengumpulan data dilakukan dengan metode angket, tes, dan dokumentasi. Hasil penelitian menyimpulkan bahwa ada pengaruh jenis kelamin terhadap sikap disiplin diri siswa; tidak ada pengaruh jenis kelamin terhadap hasil belajar Fisika siswa; tidak ada pengaruh sikap disiplin diri terhadap hasil belajar siswa.Kata kunci: jenis kelamin, sikap disiplin diri, hasil belajar fisika